1983
DOI: 10.1071/bi9830333
|View full text |Cite
|
Sign up to set email alerts
|

Antifertility Actions of a-Chlorohydrin in the Male

Abstract: Non-steroidal chemicals that affect male fertility have been known for over 25 years but only one compound, alpha-chlorohydrin, possesses most of the attributes of an ideal male contraceptive. In the male rat, for example, continuous daily oral administration of low doses produces an almost immediate and continuous antifertility response that ceases when treatment is withdrawn. Such a dose regime does not interfere with libido, is apparently not toxic and the action is specific towards mature sperm. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 61 publications
1
69
0
3
Order By: Relevance
“…In addition, data analysis suggests alterations relevant to the onset of testicular cancer. This is in good agreement with the results from previous animals studies which have convincingly shown that testis is a main target organ of 3-MCPD, especially with regard to the induction of male infertility and Leydig cell tumorigenesis (Cho et al, 2008;Jones, 1983;Kirton et al, 1970).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, data analysis suggests alterations relevant to the onset of testicular cancer. This is in good agreement with the results from previous animals studies which have convincingly shown that testis is a main target organ of 3-MCPD, especially with regard to the induction of male infertility and Leydig cell tumorigenesis (Cho et al, 2008;Jones, 1983;Kirton et al, 1970).…”
Section: Discussionsupporting
confidence: 93%
“…These inhibitory effects of 3-MCPD are reversible (Ericsson and Youngdale, 1970). At higher doses of 3-MCPD of >10e20 mg/kg body weight per day, alterations in sperm morphology and epididymal lesions are additionally observed in rats (Jones, 1983). Moreover, spermatotoxic effects of 3-MCPD are suggested to be mediated by reduced H1-ATPase expression and effects on protein kinase A signaling, leading to a disruption of sperm maturation and reduced sperm motility (Kwack et al, 2004;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Approximately 10 enzymes in this pathway have spermatogenic cell-specific isozymes (9)(10)(11)(12), including GAPDH-2 or GAPDS, a spermatogenic isoform of somatic GAPDH (12,13). This enzyme is expressed only in spermatids among the male germ cells (12)(13)(14)(15) and is a key regulator of glycolysis in spermatogenic cells concerned with male fertility (16)(17)(18). Sperm-specific antigens are potential candidates in the development of immunocontraceptives.…”
mentioning
confidence: 99%